Implementasi Pembelajaran Remedial Berbasis Proyek Pendekatan Interdisipliner Melalui Media Infografis pada Mapel IPS Fase E di MAN 2 Kota Malang - Mochammad Ronaldy Aji Saputra (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the implementation of interdisciplinary project-based remedial activities through infographic media in the Social Studies subject Phase E in class X MAN 2 Malang City after the implementation of the odd semester summative assessment. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that this activity is effective in helping students understand the Social Studies material by exploring topics in depth using relevant data and sources. In addition, students are able to understand the functions and roles of geography, sociology, history, and economics in solving real problems, strengthening research and collaboration skills, and increasing learning motivation. Teachers and students also feel the efficiency of time and resources. However, this study identified several obstacles faced by students, including difficulties in dealing with less competent group members, challenges in using barcodes as references, finding the right infographic design, classifying topics in an interdisciplinary perspective, and dividing group tasks. This study recommends infographic design training, intensive guidance for group management, and more structured learning strategies in implementing an interdisciplinary approach.